The Readiness of Australian Health Care Students to Encounter Patients Experiencing Partner Abuse. Issue 11 (June 2022) - Sawyer, Simon; Schneider, Michal; Western, Deborah; Bourke-Taylor, Helen; Farnworth, Lousie; Lawerence, Katherine; Lentin, Primrose; McLelland, Gayle; Melvin, Glenn; Recoche, Katrina; Schweitzer, Ronald; Simmonds, Janette; et al.
Partner abuse is a significant contributor to mortality and morbidity worldwide, and has been identified as a priority health care issue. Most health care students rarely receive education on partner abuse and report not feeling ready to encounter patients experiencing partner abuse. Analysis of the current readiness of health care students and can inform educational needs to address this gap. The READIness to encounter partner abuse patients Scale was delivered to a convenience sample of Australian prequalification health care students. Participant demographics and estimated hours of education were also reported. Mean readiness scores were calculated by discipline. The relationship between hours of education and readiness scores was calculated using linear regression. A total of 926 participants were included in the analysis. Approximately half of the participants (47.5%) reported less than two hours of education. Mean readiness of students was 4.99 out of 7 ( SD 0.73, range 4.39–5.95). Linear regression revealed a significant association between hours of education and readiness, r (925) = .497, p < .000. Australian health care students receive little education about partner abuse, and do not report feeling ready to encounter patients experiencing partner abuse. An individual's confidence and belief in their abilities appear to be the key factor influencing overall readiness. Participants indicated a strong belief that responding to partner abuse was part of their professional role, which is a positive change from previous research. Higher hours of education is associated with higher readiness, though which educational methodologies are most impactful remains unclear.